(untitled) (Journal of history, 2022)
Sahih Bukhari is the most important and reliable book for Muslims, especially Sunnis, after Qur’an, which contains the hadiths of the Prophet and has become increasingly popular among Muslims since its publication. This book has been written by Mohammad Ibn Ismail Bukhari, a famous and talented scientist from the land of ancient Khorasan, with many efforts and trips to different Islamic cities. In Sahih Bukhari, seven thousand and five hundred and sixty-three hadiths are included in ninety-seven books, which include three thousand nine hundred and eighteen chapters. From the time of its publication until now, many explanations and comments have been written on Sahih Bukhari. The total number of explanations, comments, translations, expulsions and other books related to Sahih Bukhari reaches hundreds of volumes written by different scientists in different countries of the world. In terms of time, immediately after the publication of this book in the fourth century, commentaries were written on it, and this commentary continues to this day. The correct descriptions of Bukhari can be divided into two categories: manuscript and print, the manuscript of which can be divided into two sections: published on virtual and unpublished sites and databases. In this article, twenty-seven descriptions of Bukhari have been studied, including twenty books that have been published, and two of the published books have been named, and five books published on Internet sites have been briefly reviewed. The abovementioned descriptions are some completed and detailed descriptions of Sahih Bukhari, others brief and concise descriptions of this book, and some are sections and books from Sahih Bukhari, and some are descriptions of one or two Sahih Bukhari books. Although the correct descriptions of the Bukhari are not limited to the few descriptions mentioned in this article, but an attempt has been made to examine and introduce the most important and famous correct descriptions of the Bukhariin this article.